2018
DOI: 10.1186/s12918-018-0665-8
|View full text |Cite
|
Sign up to set email alerts
|

Hot spot prediction in protein-protein interactions by an ensemble system

Abstract: Background: Hot spot residues are functional sites in protein interaction interfaces. The identification of hot spot residues is time-consuming and laborious using experimental methods. In order to address the issue, many computational methods have been developed to predict hot spot residues. Moreover, most prediction methods are based on structural features, sequence characteristics, and/or other protein features. Results: This paper proposed an ensemble learning method to predict hot spot residues that only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…Fortunately, predicting protein-protein interaction sites using computational methods has become a hot topic with the development of machine learning algorithms [4][5][6][7][8]. Previous studies showed that support vector machine (SVM) and its improved methods can predict effectively protein interaction sites [9][10][11][12][13][14]. Computational algorithms such as random forests, KNN, and Naive Bayes Classifier have been also applied to the prediction of PPIs [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, predicting protein-protein interaction sites using computational methods has become a hot topic with the development of machine learning algorithms [4][5][6][7][8]. Previous studies showed that support vector machine (SVM) and its improved methods can predict effectively protein interaction sites [9][10][11][12][13][14]. Computational algorithms such as random forests, KNN, and Naive Bayes Classifier have been also applied to the prediction of PPIs [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Instead, 75 vectors taken from the position-sensitive biophysical property matrix are necessary to properly split the groups, including both simple properties like charge, hydrophobicity, flexibility, and bulkiness and more carefully curated properties like the often used Kidera factors and the hotspot detecting variables of Liu et. al [39,40,54]. The inability to arrive at a core few biophysical properties that could effectively distinguish polyreactive and non-polyreactive antibodies necessitated the application of further approaches, namely information theory.…”
Section: Discussionmentioning
confidence: 99%
“…and Liu et. al [39,40]. A complete description of these properties can be found in Supplemental Table 1.…”
Section: A R N D C Q E G H I L K M F P S T W Y V a R N D C Q E G H I mentioning
confidence: 99%
“…Robetta [6,10], HotPoint [2,3,5], MAPPIS [1], KFC [11], SpotOn [12], PredHS [13], iPPHOT [14], the method using docking approach [15], HSPred [16], HEP [17]) or physico-chemical properties of their residues (e.g. method using random projection-based classifier [18], MSCA [19], method applying ensemble learning [20], DICFC [21], iFrag [22]). Most of the aforementioned algorithms require knowledge of the protein structure, which is a significant drawback of these methods because the protein structure has been determined only for a limited number of proteins.…”
Section: Methods Of Hot Spot Identificationmentioning
confidence: 99%